Iconografia das fronteiras das Guianas - Gutemberg de Vilhena Silva; Clicia Vieira Di Miceli; Brenda Farias da Silva (Confins)
This text presents an annotated iconographic record of the borders of the Guianas. The work was organized on major axes (circulation, trade and architectural pattern) so that we analyzed important issues to give visibility to the spatialities and problems by which the border cities of Guiana structure, interact and create peculiar landscapes in their geographies. We used in our observations diverse sources of data, but the photographic records of field work carried out between November and December of 2017 was the most outstanding. The central assessment is that all the complexity present at the borders of the Guianas is the result of centuries of occupation, mobilities and conflicts. In general, various institutional arrangements on a variety of topics related to that geographical space are more complex than usual, since the decisions to "open" or "close" in the border interactions consider all the political and economic dynamics that the countries have and whose reflections are felt directly or indirectly in border cities.